Socioeconomic Level of Mrs. Baduta Stunting - Nurwahyuni Nurwahyuni; Andi Nurlinda; Andi Asrina; Yusriani Yusriani (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2023)
Stunting is a chronic nutritional problem due to a lack of nutritional intake in the long term, resulting in impaired growth in children. Stunting is also one of the causes of stunted children's height, so it is lower than children their age. This study aims to determine the socioeconomic level of stunting mothers. The quantitative research design of this study sample was 27 stunting mothers, and the sampling method used total sampling. This type of research uses a descriptive method by collecting information from respondents by asking several survey questions. The results in this study are that the majority of stunting mothers are aged 20-29 years, as many as 19 people (70.4%), the majority of stunting baduta mothers' education is SMK (51.9%), the majority of stunting baduta mothers' jobs are IRT as many as 25 people (92.6%). It can be concluded that a mother's educational history affects children's growth and development, family income influences the incidence of stunting, and a mother's work involves the occurrence of stunting in children. It is expected that mothers need to increase knowledge about nutritional status in feeding children